EduSawit: Implementation of Augmented Reality in Environmentally Friendly Palm Oil Plant Education - Muhammad Ramadhan Putra Pratama; Fathoni; Muhammad Arif bin Zulkepli (Teknika, 2025)
The palm oil industry in Indonesia continues to face serious problems related to environmental degradation and small farmers limited access to information on sustainable cultivation practices. To address these challenges, this study developed EduSawit, an Augmented Reality (AR)-based educational application that supports the implementation of environmentally friendly palm oil cultivation practices. The application was designed using the Multimedia Development Life Cycle (MDLC) method, which consists of six main stages: concept formulation, design, material collection, assembly, testing, and distribution. Its main feature is interactive 3D visualization that displays important processes such as site selection, provision of superior seeds, mixed planting patterns, use of organic fertilizers, water management, biological pest control, and palm oil waste management. Validation was carried out using Black Box testing to ensure that all functions, including AR marker scanning, 3D object display, and information panels, worked as expected. The research results show that EduSawit is a technically reliable and pedagogically relevant learning medium, with the potential to improve farmers understanding of sustainable cultivation practices. The next step is a field trial with smallholder farmers to assess the application's effectiveness in increasing knowledge, confidence, and adoption of environmentally friendly practices.